MASYARAKAT MUSLIM DI TENGAH KRISIS POLITIK: RESISTENSI MASYARAKAT NAGARI DILAM PASCA PERANG PRRI (1958-1965) - Melia Afdayeni (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
This research was motivated by the PRRI war that took place in Sumatra Batar in 1958- 1961 AD, this war was known as the civil war, because it was the central army or APRI who fought against the PRRI soldiers who came from West Sumatra. This war involved all the people in Minangkabau, without exception the people living in the Dilam village. This war caused a very severe impact on the lives of the people of Nagari Dilam, apart from material losses, the community also suffered psychological losses. After realizing that PRRI was repulsed by APRI, they left the nagari and hid in the forests of West Sumatra. The people of Nagari Dilam really feel how tense it is to live in a nagari that is continuously monitored by the OPR (Operation for the People's Security), to deal with this situation, the community has put up resistance (resistance) by returning to the mosque and surau. For this reason, this paper aims to explore the forms of resistance carried out by the community and explore the reasons for the Dilam village community to testify. To answer the existing problems, it takes stages of resistance research commonly used in historical research including: heuristics (Source Collection), source criticism, interpretation and the last is historiography (Writing). This research results that the form of resistance carried out by the Dilam nagari community is to return to the mosque and surau to study and explore Islam, which they have long adhered to, while the reason the Dilam nagari community carries out this resistance is: First, the community is afraid of OPR which often exerted pressure and intimidation against them. Both communities were afraid of the frequent killings carried out by the OPR against PRRI soldiers, and vice versa. The three inter-community killings became commonplace because there was no punishment for those who committed the killings.